Modifikasi Kurikulum untuk Mengakomodasi Pendidikan Inklusif Tingkat Sekolah Dasar - Pambayun, Mutiara Wahyu Sekar; Salma, Yuniar Qoniah; Rhomadhoni, Novela Qona’ah Nur; Minsih, Minsih (Jurnal Likhitaprajna, 2025)
The curriculum has an important role as a guide for future education so that it is implemented optimally. Curriculum modification is a strategy used to accommodate the needs and abilities of regular students. Therefore, this article aims to describe how curriculum modifications are implemented to accommodate inclusive education at Al-Firdaus Elementary School, describe the evaluation and challenges experienced in implementing curriculum modifications in inclusive education at Al-Firdaus Elementary School. This article was written using qualitative methods by analyzing phenomena experienced by research subjects descriptively using words to describe actual conditions. Data collection techniques were carried out through observation and interviews. The results of this research indicate that implementing curriculum modifications at Al-Firdaus Elementary School is a crucial step in supporting inclusive education. The curriculum, which has been modified since 2006, has accommodated the needs and abilities of each student, with a modification process involving identification, assessment and adjustment. Even though it has become an important part of inclusive education management, challenges such as lack of parental support and insufficient understanding from some teachers remain. However, the comprehensive evaluation carried out by the internal evaluation team has helped Al-Firdaus Elementary School to continue to improve and develop its inclusion program to provide fair and quality education for all its students.